Resposta de genótipos de arroz (Oryza sativa L.) ao estresse por ácidos orgânicos sob condições de ambiente controlado - Kopp, Mauricio Marini (2008)
Hydromorphic soils present as main feature a reduced natural drainage ability, being mostly used for growing irrigated rice. Thus, the occurrence of anaerobic conditions associated to the presence of organic matter enables the development of anaerobic microorganisms which, while decomposing the organic matter, generate phytotoxic substances represented mainly by short chain aliphatic organic acids. The selection of promising genotypes adapted for use in these situations requires complicated field evaluations, which can be simulated under hydroponic culture. The research was composed of four articles that had as major goals to establish an adequate methodology for growing rice under organic acid rich hydroponic culture. The first work aimed at determining the range of concentrations and response variables most indicated for evaluating rice genotypes under hydroponics. The effects of six different concentrations for the three major acids formed in the soil: acetic (0; 4; 8; 12; 16 and 20 mM), propionic (0; 3; 6; 9; 12 and 15 mM) and butyric (0; 2; 4; 6; 8 and 10 mM) acids in two genotypes of high divergence (BRS 7-TAIM and SAIBAN). The results indicated that the most adequate concentration range for organic acid studies in rice are between 15.8 and 8.4; 9.1 and 4.2 and 7.7 and 3.7 mM for acetic, propionic and butyric acids, respectively. Also, the most responsive variable was root length. The second experiment had as goal to determine, under hydroponics, the influence of the pH level used in the hydroponic solution on the phytotoxicity caused by acetic, propionic and butyric acids in rice, as well as the performance of some variables currently used in studies of abiotic stress tolerance in hydroponic systems. For this experiment, three acids (acetic, propionic and butyric) and four pH (4.0; 5.0; 6.0 and 7.0) levels were evaluated. The results allow one to conclude that reduced pH levels increase the phytotoxicity of all acids. The root and shoot lengths have independent behavior from the acid used, as opposite to root number and root and shoot dry matter. Root length was the variable most affected by the treatments. The third article had as objective to evaluate the response of 25 rice genotypes to the phytotoxic effect of acetic, propionic and butyric acids, individually. In this work, 4 treatments were used for each acid: 0 (control); 4; 8 and 12 mM for acetic; 0; 3; 6 and 9 mM for propionic and 0; 2; 4 and 6 mM for butyric acid, respectively. The variables measured were root (CR) and shoot (CPA) length, root number (NR) and root (MSR) and shoot (MSPA) dry matter. The relative performance of the variable CR was the most affected by the acids and the regressions established for this variable revealed ix ix tolerant and sensitive genotypes to organic acids, with 6; 6 and 9 tolerant genotypes for acetic, propionic and butyric acids, respectively. It was observed a higher number of tolerant genotypes on the japonica than on the indica group. The fourth experiment had as objective to evaluate the response of 20 rice cultivars to the interactive phytotoxic effect of acetic, propionic and butyric acids. In these work, four treatments, 0 (control); 3; 6 and 9 mM were used, consisting of the mixture of three acids (acetic, propionic and butyric) at a 6:3:1 ratio. The variables measured were root (CR) and shoot (CPA) length, root number (NR) and root (MSR) and shoot (MSPA) dry matter, phosphorus (P) and potassium (K) content. The results indicated significant differences between the genotypes evaluated for the characters CR, CPA, P and K. Four genotypes were ranked as tolerants. The variable CR associated to CPA, P and K are indicated for the selection of tolerant genotypes. The results obtained allowed one to establish an adequate methodology for the selection of rice genotypes under hydroponic systems combined with organic acid stress (acetic, propionic and butyric) as well as to select promising genotypes regarding their response to this stress.